Range Hood and Make-up Air Supply System to Prevent Dispersion of Cooking-generated Particulate Matter - Hyungkeun Kim; Kyungmo Kang; Taeyeon Kim (Aerosol and Air Quality Research)
Abstract Cooking is a major contributor to indoor particulate matter (PM) concentrations. Studies suggest that cooking-generated PM rapidly disperses even when a range hood is in operation, suggesting that range hoods fail to perform sufficiently when used in isolation. However, the performance of range hoods can be improved by a supply of make-up air equivalent to the airflow rate of the range hood. This study evaluates the prevention of the dispersion of cooking-generated PM and the discharge performance when a range hood and ventilation system are integrated. Three operation strategies were established, and the PM concentration was measured to estimate the effect of particle dispersion. An auxiliary supply system (AS) and supply of heat recovery ventilator (HRV) were used for the make-up air supply. The integrated operation of the AS and range hood was effective in preventing PM dispersion during cooking, thereby reducing the maximum PM concentrations by 54.6% and 75.1% in the kitchen and living room of the experimental house, respectively. The integrated operation of the HRV and range hood was more effective in discharging dispersed PM after cooking. Based on the results of this study, it is recommended that the integrated application of a range hood and make-up air is applied during and after cooking.